Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.amjmed.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Electrolyte Disorders, Syncope, and Falls in Patients Taking Thiazide Diuretics: Results of a Cross-Sectional Study

Abstract: BACKGROUND: Thiazide diuretics are a mainstay in the management of hypertension and often associated with dyselectrolytemias. We investigated the prevalence of and risk factors for hyponatremia and hypokalemia in thiazide users, substance-specific differences, and the association of thiazides with syncope and falls. METHODS: In this cross-sectional analysis all patients admitted to an interdisciplinary emergency department in Switzerland between January 1, 2017, and December 31, 2018, with measurements of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The association of VD reflex syncope with chronic vasoactive drug therapy is a frequent clinical problem, especially in the elderly. The use of thiazides has been shown to be an independent predictor for syncope even after correction for age and the presence of hyponatremia and hypokalemia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association of VD reflex syncope with chronic vasoactive drug therapy is a frequent clinical problem, especially in the elderly. The use of thiazides has been shown to be an independent predictor for syncope even after correction for age and the presence of hyponatremia and hypokalemia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In reply to the letter from Pareek et al on our study 1 on the association between thiazide diuretic use and the prevalence of electrolyte disorders, syncope, and falls we would like to state the following: Our analysis of a large, real-life collective of patients clearly showed that thiazide diuretics were a strong risk factor for the presence of hyponatremia as well as hypokalemia. Of course, the study is a cross-sectional analysis and its results imply an association and not causality.…”
Section: The Replymentioning
confidence: 89%
“…While hyponatremia has a broad spectrum of etiologies, of which the syndrome of inadequate antidiuretic hormone secretion, low effective circulating volume through heart failure or cirrhosis of the liver or diuretics are amongst the most common [ 11 , 12 ]. Hypernatremia in outpatients on the other hand, is mainly caused by an inadequate intake of electrolyte-free water, due to a lack of access or an impaired sense of thirst, caused by a central nervous system pathology, medication or intoxication [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%